Improving The Efficiency Of Mastering The Programming Language Based On Game Technologies (Journal of Pedagogical Inventions and Practices, 2024)
This article deals with the information about specific techniques and methods that allow improving the use of interactive methods in the educational process in higher education institutions, increasing the effectiveness and quality of education, that is, making the lesson unusual, richer and more interesting. The author assumes that interactive education allows students to actively participate in the learning process in order to get the most information and knowledge from their teachers, as well as use various methods of presentation of practical demonstrations and exercises